Inflation stabilization and welfare the case of a distorted steady state - Benigno, Pierpaolo 1971-; Woodford, Michael 1955- (National Bureau of Economic Research, 2004)
This paper considers the appropriate stabilization objectives for monetary policy in a microfounded model with staggered price-setting. Rotemberg and Woodford (1997) and Woodford (2002) have shown that under certain conditions, a local approximation to the expected utility of the representative household in a model of this kind is related inversely to the expected discounted value of a conventional quadratic loss function, in which each period's loss is a weighted average of squared deviations of inflation and an output gap measure from their optimal values (zero). However, those derivations rely on an assumption of the existence of an output or employment subsidy that offsets the distortion due to the market power of monopolistically-competitive price-setters, so that the steady state under a zero-inflation policy involves an efficient level of output. Here we show how to dispense with this unappealing assumption, so that a valid linear-quadratic approximation to the optimal policy problem is possible even when the steady state is distorted to an arbitrary extent (allowing for tax distortions as well as market power), and when, as a consequence, it is necessary to take account of the effects of stabilization policy on the average level of output.
Keywords: Economic policy; Economic stabilization; Inflation (Finance); Welfare economics; Inflationsbekämpfung / Geldpolitik / Mikroökonomische Fundierung / Wohlfahrtseffekt / Steady-State-Wachstum / Erwartungsnutzen / Theorie; Wirtschaftspolitik